2016
DOI: 10.1038/srep29338
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of rheumatoid arthritis reveals a linkage between HLA-DRB1 genotype, CXCR4 expression on memory CD4+ T cells and disease activity

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease that leads to destructive arthritis. Although the HLA class II locus is the strongest genetic risk factor for rheumatoid arthritis, the relationship between HLA class II alleles and lymphocyte activation remains unclear. We performed immunophenotyping of peripheral blood mononuclear cells on 91 HLA-DRB1-genotyped RA patients and 110 healthy donors. The frequency of memory CXCR4+CD4+ T cells, and not Th1 and Th17 cells, was significantly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 63 publications
(71 reference statements)
4
41
0
4
Order By: Relevance
“…When we examined PDCD1 expression, over‐expression was associated with RA, not under‐expression. This finding was in contrast to our original hypothesis but was consistent with previous studies showing increased T‐cell activation in RA, activation‐induced PDCD1 expression in T lymphocytes and increased PDCD1 protein levels in RA . This prompted us to investigate whether PDCD1 polymorphism may account for altered PDCD1 expression in RA.…”
Section: Discussionsupporting
confidence: 90%
“…When we examined PDCD1 expression, over‐expression was associated with RA, not under‐expression. This finding was in contrast to our original hypothesis but was consistent with previous studies showing increased T‐cell activation in RA, activation‐induced PDCD1 expression in T lymphocytes and increased PDCD1 protein levels in RA . This prompted us to investigate whether PDCD1 polymorphism may account for altered PDCD1 expression in RA.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of HLA-DR was not confined to activated CD4+ and CD8+ T cells [14]. Nagafuchi et al [15] studied immunophenotyping of peripheral blood mononuclear cells on RA patients with HLA-DRB1genotype and found the frequency of memory CXCR4+CD4+ T cells was significantly related to severity of disease. A significantly higher frequency of memory CXCR4+CD4+ T cells was found in the patients with one or more susceptible HLA-DR haplotypes, moreover, on B cells, the frequency of memory CXCR4+CD4+ T cells significantly was associated with the HLA-DR expression, which suggested that the interaction between HLA-DR and T cell receptors can regulate the memory CXCR4+CD4+ T cells.…”
Section: Introductionmentioning
confidence: 99%
“…A, Data from the Roadmap Epigenomics Project , indicating that rs12529514 resides near a DN ase hypersensitivity site in B cells and alters an NF ‐κB binding site close by. B, Flow cytometric analysis of peripheral blood from 106 healthy donors . Plots indicate the frequencies of B cell subsets by rs12529514 genotype.…”
mentioning
confidence: 99%
“…CD83 regulates the development of murine B cells . We therefore hypothesized that CD83 expression might influence the development of human B cells, and we examined the relationship between this haplotype and peripheral blood B cells in healthy subjects from our data set . Individuals with the RA risk SNP had an increased frequency of CD27−IgD− double‐negative B cells (Figure B), a subset that is increased in the peripheral blood of RA patients and thought to be pathogenic .…”
mentioning
confidence: 99%
See 1 more Smart Citation